(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
This study investigates the intricate relationship between corporate governance, capital structure, and firm performance in the context of listed firms. A quantitative research approach was employed, utilizing data that includes Return on Assets (ROA), leverage ratios as indicators of capital structure, and corporate governance variables such as board composition, executive compensation, and regulatory compliance. Regression analysis was conducted, accounting for control variables such as firm size, industry sector, and macroeconomic conditions. The results indicate a positive relationship between corporate governance and ROA, suggesting that stronger governance mechanisms are associated with higher profitability, consistent with findings from previous studies. Conversely, the analysis reveals a negative relationship between capital structure and ROA, indicating that higher leverage is linked to lower profitability, thereby supporting the pecking order theory. However, the study’s methodology presents certain limitations, including reliance on cross-sectional data, the potential for omitted variable bias, and limited generalizability within the Pakistani context. While the findings offer valuable insights for policymakers, practitioners, and scholars in the fields of corporate finance and governance, caution should be exercised when generalizing these results to countries with different institutional contexts and market structures.